Return Migration and Self-Employment: Evidence from Kyrgyzstan - Tilman Brück; Clotilde Mahe; Wim Naudé (Institute of Labor Economics (IZA), 2018)
A common finding of the migration literature is that migrants are more likely to choose self-employment upon return to their origin countries than non-migrants. This has led to the belief that return migration stimulates entrepreneurship in source countries and hence supports economic development. In this paper, we test these assertions, drawing on the Life in Kyrgyzstan Study, a rich longitudinal data set from a transition economy with high levels of international temporary migration. We find that for return migrants, self-employment is often a temporary occupational choice, suggesting that self-employment serves as a 'parking lot'. In addition, we find evidence that return migrants who were self-employed before migrating are less likely to opt for self-employment on their return, implying that migration disrupts self-employment trajectories. Both findings cast doubt on the common narrative of return migration stimulating entrepreneurship and therefore economic development.
Keywords: F22; J24; L26; P20; 330; occupational choice; entrepreneurship; migration; transition economies; Central Asia; Kyrgyzstan